ANALISIS PENDAPATAN USAHA PETERNAKAN AYAM PETELUR SUMUR BANGER FARM KECAMATAN TERSONO KABUPATEN BATANG - Firdaus Hidayat Maulana; E Prasetyo; Warsono Sarengat (MEDIAGRO, 2017)
A research aims (i) to calculated the variable cost in a farm hen laying chicken which include feed cost, sanitation and vaccines cost, employer cost, and marketing cost on every month. (ii) to calculated effort of income hen laying chicken on every month per year. (iii) to analysis influence of total population of hen laying chicken, total production egg, feed cost, sanitation and vaccines cost, employer cost, and marketing cost to effort of income hen laying chicken farm. This research implemented at Sumur Banger Farm in Sumur Banger Village, Tersono District, Batang Regency. The data collection in this research using the interview and observations. The kind of data collected is the primary data and data secondary. The data primary in the form of the data “time series” for 3 years of the period of the production of 2013, 2014 and 2015. A quantitative analysis tested using analysis linear regression. Based on research results are known to the variable cost Sumur banger Farm on breed as 35760, 35676, and 35870 chickens for 2013-2015 reached the value of Rp 5.803.076.721; Rp 6.572.239.037; Rp 7.241.422.443, while variable of cost per month on the year 2013 reached Rp 393.589.727, in 2014 reached Rp 453.686.586, and in 2015 reached Rp 505.451.870. Total revenue at Sumur Banger Farm in 2013 reached Rp 3.143.597.467, in 2014 Rp 2.988.318.193 and in 2015 Rp 3.011.419.770, while revenue each month on the year 2013 reached Rp 261.966.456, in 2014 Rp 249.026.516 and in 2015 Rp 250.951.648. Based on analysis linear regression the variables that significantly partially on poultry layer farm business income is the amount of egg production (sig 0,000<0,05) and marketing cost (sig 0,000<0,05). Then for partial values that do not significantly affect the revenue that is population of hen laying chicken (sig 0,447>0,05), feed cost (sig 0,404>0,05), vaccines cost (sig 0,621>0,05), and employer cost (sig 0,111>0,05). Keywords:  Variable Cost, Layer Poultry, Revenue.